2015
DOI: 10.3390/f6062082
|View full text |Cite
|
Sign up to set email alerts
|

Early Differential Responses of Co-dominant Canopy Species to Sudden and Severe Drought in a Mediterranean-climate Type Forest

Abstract: Globally, drought and heat-induced forest disturbance is garnering increasing concern. Species from Mediterranean forests have resistance and resilience mechanisms to cope with drought and differences in these ecological strategies will profoundly influence vegetation composition in response to drought. Our aim was to contrast the early response of two co-occurring forest species, Eucalyptus marginata and Corymbia calophylla, in the Northern Jarrah Forest of southwestern Australia, following a sudden and sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…; Ruthrof et al . ), and studies have increased our understanding of the physiological mechanisms of tree mortality (Mencuccini et al . ; Davi & Cailleret ), there is still a lack of knowledge of drought‐induced mortality responses of different tree functional strategies at a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…; Ruthrof et al . ), and studies have increased our understanding of the physiological mechanisms of tree mortality (Mencuccini et al . ; Davi & Cailleret ), there is still a lack of knowledge of drought‐induced mortality responses of different tree functional strategies at a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Plots were visited during June and July 2011, 3 months following the first observations of forest die-off, to measure the forest structure, severity and patterns of the die-off Ruthrof et al 2015), and plots were revisited in July 2012, 16 months post-drought, to measure surface fuels.…”
Section: Site Selectionmentioning
confidence: 99%
“…While we have previously shown that the drought had a higher immediate impact on E. marginata , compared to C. calophylla (Ruthrof et al. ). Here, we found no direct evidence for longer‐term changes in the proportional abundance of the two species over the measurement period, suggesting losses by both species were similar.…”
Section: Discussionmentioning
confidence: 67%